Natural products of traditional Chinese medicine treat atherosclerosis by regulating inflammatory and oxidative stress pathways - Meng, Tianwei; Li, Xinghua; Li, Chengjia; Liu, Jiawen; Chang, Hong; Jiang, Nan; Li, Jiarui; Zhou, Yabin; Liu, Zhiping (Frontiers in Pharmacology, 2022)
Atherosclerosis (AS) is a common arteriosclerotic vascular disease. It is also an important pathological basis for coronary heart disease, stroke, and other diseases. Inflammatory responses and oxidative stress responses are throughout the development of AS formation. In the past few decades, the treatment strategy for AS has mainly focused on the use of high-intensity statins to reduce blood lipid levels, but the damage to liver and kidney function caused by long-term use is inevitable. In China, natural medicines are widely used in the prevention and treatment of AS because of their wide range of effects and small toxic and side effects. With the keywords of "atherosclerosis, traditional Chinese medicine, natural compounds, inflammation, and oxidative stress", relevant pieces of literature in the past five years were searched in databases such as PubMed. The results showed that PI3K/ AKT, TLR4, JAK/STAT, Nrf2, MAPK, and NF-κB were the most relevant inflammatory and oxidative stress pathways in AS. In addition, this paper summarizes the mechanism studies of natural medicines of alkaloids, flavonoids, polyphenols, saponins, and quinones against AS through these pathways. This study aims to update and summarize the research progress of natural medicines in the treatment of AS by acting on inflammatory and oxidative stress-related signaling pathways, and to provide an information basis for the development of effective drugs for the treatment of AS in the future.